Vaccine-associated enhanced disease in humans and animal models: Lessons and challenges for vaccine development - Bigay, Julie; Le Grand, Roger; Martinon, Frédéric; Maisonnasse, Pauline (Frontiers in Microbiology, 2022)
The fight against infectious diseases calls for the development of safe and effective vaccines that generate long-lasting protective immunity. In few situations, vaccine-mediated immune responses may have led to exacerbated pathology upon subsequent infection with the pathogen targeted by the vaccine. This vaccine-associated enhanced disease (VAED) has been reported, or at least suspected, in human or animal models for vaccine candidates against the Respiratory Syncytial Virus (RSV), the Measles Virus (MV), the Dengue Virus (DENV), the Human Immunodeficiency Virus-1 (HIV-1) and Simian Immunodeficiency Virus (SIV), the Severe Acute Respiratory Syndrome Coronavirus 1 (SARS-CoV-1) and the Middle East Respiratory Syndrome Coronavirus (MERS-CoV). Although discarded by clinical and epidemiological evidences, some concerns were also initially raised regarding short and long-term safety of vaccines against the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) that is causing the ongoing coronavirus-induced disease 2019 (COVID-19) pandemic. While the mechanisms leading to this phenomenon are not yet completely understood, the individual and/or collective role of antibody-dependent enhancement (ADE), complement-dependent enhancement and cell-dependent enhancement have been highlighted. Here we review mechanisms that may be associate with risks of VAED, and that are important to take into consideration both in the assessment of vaccine safety, and in finding ways to define immunization strategies that prevent this concern.